Pengaruh Tingkat Pengetahuan Keuangan, Sikap Keuangan dan Kepribadian Terhadap Perilaku Manajemen Keuangan - Ahmad Albar Tanjung; Risma Agus Triyani (Owner : Riset dan Jurnal Akuntansi, 2023)
ABSTRACT The cause of the lack of awareness of MSME actors in budget planning is the perception of MSME actors that budget planning is not important and easy to manage and does not have a negative impact on the sustainability of their business operations obtained from data from the Financial Services Authority. This study aims to determine the influence of financial knowledge level, financial attitude and personality on financial management behavior in MSMEs in Medan City. This research was conducted by Micro, Small and Medium Enterprises (MSMEs) located in Medan City, totaling 96 MSMEs. The time of this study was carried out from March to completion. In this study 96 samples were obtained, samples obtained by distributing questionnaires as a form of data collection. The sampling technique used is based on the size of the sample using the formula of Isaac and Michael. The data analysis method used is structural equation modeling partial least square. The results showed that financial knowledge has a positive and significant influence on financial management. Financial attitudes have a positive and significant effect on financial management. The results showed that personality has a positive and significant effect on financial management.